Confucianism: An Approach to Education for Morality and Rationality - Lam, Chi-Ming, (Brill Research Perspectives in Humanities and Social Sciences ;, 2025)
How can ancient Confucian wisdom shape today's education for morality and rationality? This book bridges the past and present, examining Confucian virtues such as humility and reflection alongside Karl Popper's falsificationism to uncover pathways for fostering critical thinking and ethical responsibility. Readers will explore how Confucian principles challenge the myth of incompatibility with rationality and discover their transformative potential for cultivating open-minded, critically engaged citizens. Rich with philosophical insights and practical applications for educators, this book offers a compelling roadmap for integrating traditional values into modern educational practices. A must-read for educators, philosophers, and anyone seeking new directions in moral education.